2022
DOI: 10.1111/aji.13631
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic deviations in recurrent spontaneous abortion mouse model

Abstract: Background Recurrent spontaneous abortion (RSA) or recurrent pregnancy loss (RPL) is an abnormality that has a great impact on women's quality of life. RSA is defined as at least three unexplained abortions (without prior live birth) occurring before the 20th week of pregnancy. Aim The present review attempts to discuss immunologic deviations in mouse models of RSA. Content The mating of DBA/2J males with CBA/J female mice has provided specialists with a homologous model of RSA. Much of the research using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Recurrent spontaneous miscarriage (RSM) refers to two or more consecutive spontaneous abortions with the same spouse before the 20th week of gestation [ 1 ]. RSM accounts for approximately 2–5% of the total pregnancies [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent spontaneous miscarriage (RSM) refers to two or more consecutive spontaneous abortions with the same spouse before the 20th week of gestation [ 1 ]. RSM accounts for approximately 2–5% of the total pregnancies [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under these circumstances, it is crucial to identify factors that indicate a high risk for the presence of CE. [18][19][20][21][22] Analysis of these factors will allow targeted selection of patients for hysteroscopy or other methods of endometrial biopsy, thereby increasing the eff ectiveness of diagnostic eff orts.…”
Section: Introductionmentioning
confidence: 99%
“…Complex immunological processes at the maternal-fetal interface have been mainly studied in rodent models. Preclinical studies have shown that the equilibrium of T-, B-and uterine natural killer (NK) cells (9) and the production of immunosuppressive cytokines by regulatory T cells (10) is important in a typical pregnancy. These models have also shown that a shift in T-helper (Th) cell balance towards increased Th1 cells, complement activation and the depletion of regulatory T cells or NK cells may all lead to adverse pregnancy outcomes, including fetal rejection, impaired fetal growth, and abnormal neurodevelopment (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%